2012
DOI: 10.1021/pr300562m
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Fingerprints of Serum, Brain, and Liver Are Distinct for Mice with Cerebral and Noncerebral Malaria: A 1H NMR Spectroscopy-Based Metabonomic Study

Abstract: Cerebral malaria (CM) is a life-threatening disease in humans caused by Plasmodium falciparum, leading to high mortality. Plasmodium berghei ANKA (PbA) infection in C57Bl/6 mice induces pathologic symptoms similar to that in human CM. However, experimental CM incidence in mice is variable, and there are no known metabolic correlates/ fingerprints for the animals that develop CM. Here, we have used 1 H NMR-based metabonomics to investigate the metabolic changes in the mice with CM with respect to the mice that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 57 publications
4
45
1
Order By: Relevance
“…Upon reintegration of GDE1, internal metabolites returned to levels similar to wild type. These results indicate that both Git3 and Gde1 are active in the presence of serum, which is known to contain GroPCho (14,15,43).…”
Section: Kinetics Of Gropcho Transport By Git3 and Git4-givenmentioning
confidence: 70%
“…Upon reintegration of GDE1, internal metabolites returned to levels similar to wild type. These results indicate that both Git3 and Gde1 are active in the presence of serum, which is known to contain GroPCho (14,15,43).…”
Section: Kinetics Of Gropcho Transport By Git3 and Git4-givenmentioning
confidence: 70%
“…Metabolomic studies have been reported that are of relevance to Wilson's disease [103, 104], primary biliary cirrhosis [105], primary sclerosing cholangitis [105], the hepatic stage of malaria [106108], as well as various aspects of hepatic encephalopathy [109112]. …”
Section: The Metabolomic Window Into Other Hepatobiliary Diseasesmentioning
confidence: 99%
“…Nuclear magnetic resonance or gas/liquid chromatography coupled with mass spectrometry (GC/LC-MS) have been applied to understand the metabolic changes in models of host- Plasmodium interactions in vitro (Lakshmanan et al, 2012; MacRae et al, 2013; O’Hara et al, 2014; Olszewski et al, 2009; Park et al, 2015; Sana et al, 2013) and in vivo (Basant et al, 2010; Ghosh et al, 2012, 2013; Olszewski et al, 2009; Sengupta et al, 2013; Tritten et al, 2013). However, studies of human malaria are limited to evaluation of plasma from patients infected with P. falciparum (Lakshmanan et al, 2012; Surowiec et al, 2015; Sengupta et al, 2016) or urine from patients infected with P. vivax (Sengupta et al, 2011).…”
Section: Introductionmentioning
confidence: 99%